Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.5194/npg-28-167-2021
|View full text |Cite
|
Sign up to set email alerts
|

Size distribution law of earthquake-triggered landslides in different seismic intensity zones

Abstract: Abstract. The Ms 8.0 Wenchuan earthquake in 2008 and Ms 7.0 Lushan earthquake in 2013 produced thousands of landslides in the southern region of the Longmen Mountains in China. We conducted field investigations and analyzed remote sensing data to determine the distribution law of earthquake-triggered landslides. The results show a strong negative power law relationship between the size and frequency of landslides in VII, VIII, and IX seismic intensity zones, a weak power law in the X seismic intensity zone, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 46 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…The main direction of the maximum horizontal principal stress in the south section of the Longmenshan fault zone is NW (Meng et al 2015). Although the magnitude of the Lushan earthquake is lower than that of the Wenchuan Mw7.9 earthquake, the secondary disasters triggered by the Lushan earthquake can not be neglected due to the influence of terrain (Huang et al 2021).…”
Section: Introduction To Lushan Earthquakementioning
confidence: 99%
“…The main direction of the maximum horizontal principal stress in the south section of the Longmenshan fault zone is NW (Meng et al 2015). Although the magnitude of the Lushan earthquake is lower than that of the Wenchuan Mw7.9 earthquake, the secondary disasters triggered by the Lushan earthquake can not be neglected due to the influence of terrain (Huang et al 2021).…”
Section: Introduction To Lushan Earthquakementioning
confidence: 99%
“…From the 1900s to the 2010s, much effort has been devoted to investigating the relationship between earthquake-triggered landslides and the possible impact factors (Keefer, 1984;Rodriguez et al, 1999;Mahdavifar et al, 2006). These studies have shown that the factors that have a great in uence on earthquake-triggered landslides are the topographical factors (Yagi et al, 2009;Yuan et al, 2015;Serey et al, 2019), the geological structure (Mahdavifar et al, 2006;Sato et al, 2007;Huang et al, 2009), the ground shaking parameters (Meunier et al, 2007;Nowicki et al, 2014;Huang et al, 2021) . Many scholars have used remote sensing images from before and after the earthquake to identify post-seismic landslides and generate earthquake-triggered landslide inventories (ETLIs) (Sato et al, 2007;Wartman et al, 2013;Valkaniotis et al, 2018;Ferrario, 2019).…”
Section: Introductionmentioning
confidence: 99%